2020
DOI: 10.3329/bjid.v7i00.50158
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Characteristics of 1082 Positive Cases of COVID-19 Patients: Experience at National Referral Laboratory of Bangladesh

Abstract: Background: COVID-19 has now become a pandemic. Objective: The aim of this study was to characterize the demographic features with infection rate of SARS-CoV-2 in 4/5 divisions of Bangladesh. Methodology: This cross-sectional study was conducted at National institute of Laboratory Medicine and Referral Center, Dhaka, Bangladesh from 15th April to 30th April, 2020. It was performed RT-PCR for 2462 cases within the time frame and 1082 samples were positive for SARS CoV-2. Patient demographic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 11 publications
1
10
1
Order By: Relevance
“…Current study found that most of the patients were in the age group of 21-40 (67.2%) and this finding was similar to two studies conducted in Bangladesh 19,20 but contrary to another study done in Bangladesh and also in China. 21,13 Mean age of study population was 34.3 ± 12.2 and that was concordance with studies conducted in Bangladesh and India.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Current study found that most of the patients were in the age group of 21-40 (67.2%) and this finding was similar to two studies conducted in Bangladesh 19,20 but contrary to another study done in Bangladesh and also in China. 21,13 Mean age of study population was 34.3 ± 12.2 and that was concordance with studies conducted in Bangladesh and India.…”
Section: Discussionsupporting
confidence: 79%
“…Similar male predominance was also found in several studies. 13,18,19,20,21,22,23,24,26 Most of the patients (85.4%) of the current study had no comorbidities and 14.6% have one or more comorbidities. And that was similar to studies conducted by in Bangladesh and India.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The virus spread globally so rapidly that about 221 countries (by 20 th September, 2021) have already been facing its grave consequences 4 . As of 20 th September 2021, 221 countries, including Bangladesh have confirmed more than 228.21 million COVID-19 cases and 4.68 million deaths globally 5 .In Bangladesh, the first three confirmed cases of COVID-19 were reported on 8 th march, 2020 by the Institute of Epidemiology, Disease Control and Research (IEDCR) 6,7 . Almost every country of the world had adopted aggressive therapeutic and nontherapeutic measures to control the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%